Global ecosystem-based strategy of international firm under conditions of increasing technological dynamism - Danko, Taras (Szkoła Główna Handlowa w Warszawie, Polska, 2023)
The paper explores the impact of increasing technological dynamism on international firms. It emphasizes the growing importance of innovation ecosystems for firm success in a rapidly evolving technological landscape. The paper proposes and preliminarily tests a framework for an ecosystem-based strategy for international firms under high technological dynamism. It examines key considerations for multinational corporations (MNCs) in adopting such strategies, their implementation, and the outcomes and performance implications. The study uses a retrospective case study methodology, focusing on the manufacturing execution systems market as an illustrative example. The findings suggest that participation in global innovation ecosystems is crucial for the continuous success and resilience of international firms in this dynamic environment.
Глобальна екосистемна стратегія міжнародної фірми в умовах підвищення технологічної динамічності
Keywords: ecosystem-based strategy; ecosystem-specific advantages; global innovation ecosystems; international firm; technological dynamism